Persepsi Siswa Terhadap Penerapan Model Pembelajaran Project Based Learning Menggunakan Alat Peraga Pada Materi Sistem Pernapasan Manusia di Kelas XI SMAN 1 Bunobogu - Indri A. Artinya; Bustamin; Abd. Rauf; Mursito S. Bialangi; Syech Zainal; Moh. Sabran (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe students’ perceptions of the implementation of the Project -Based Learning (PjBL) model combined with the use of teaching aids in learning the human respiratory system in Grade XI at SMAN 1 Bunobogu. The study employed a descriptive qualitative approach. The research subjects consisted of three students purposively selected based on different levels of ability. Data were collected through participatory observation, in-depth interviews, supporting questionnaires using a Likert scale, and documentation. Data validity was ensured through source and method triangulation, while data analysis followed the Miles and Huberman model. The results indicate positive perceptions across all three aspects. The cognitive aspect showed a supporting questionnaire score of 3.56 (good category), and the teaching aids effectively transformed abstract concepts into more concrete representations. The affective aspect, with a score of 3.58, reflected increased learning interest and motivation. The psychomotor aspect, with a score of 3.53, contributed to the development of practical skills, creativity, and teamwork.